Criss-Crossing Migration - Mattoo, Aaditya (World Bank, Washington, DC, 2013)
The current perspective on the flow of people is almost exclusively focused on permanent migration from poorer to richer countries and on immigration policies in industrial countries. But international mobility of people should no longer be seen as a one-time event or one-way flow from South to North. The economic crisis has accentuated the longer-term shift in location incentives for people in industrial countries. As consumers, they could obtain better and cheaper access to key services -- such as care for the elderly, health, and education -- whose costs at home are projected to increase in the future, threatening standards of living. As workers, they could benefit from new opportunities created by the shift in economic dynamism from industrial to emerging countries. But subtle incentives to stay at home, such as lack of portability of health insurance and non-recognition of qualifications obtained abroad, inhibit North-South mobility and need to be addressed. Furthermore, if beneficiaries of movement abroad exert countervailing power against those who support immigration barriers at home, then that could lead to greater inflows of people, boosting innovation and growth in the North. Eventually, growing two-way flows of people could create the possibility of a grand bargain to reduce impediments to the movement of people at every stage in all countries and help realize the full benefits of globalization.